2022
DOI: 10.1101/2022.01.25.477616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visible blue light inactivates SARS-CoV-2 variants and inhibits Delta replication in differentiated human airway epithelia

Abstract: The emergence of SARS-CoV-2 variants that evade host immune responses has prolonged the COVID-19 pandemic. Thus, the development of an efficacious, variant-agnostic therapeutic for the treatment of early SARS-CoV-2 infection would help reduce global health and economic burdens. Visible light therapy has the potential to fill these gaps. In this study, visible blue light centered around 425 nm efficiently inactivated SARS-CoV-2 variants in cell-free suspensions and in a translationally relevant well-differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Sunlight exposure may serve to decontaminate SARS‐CoV‐2 experimentally, but will depend on the specific virus milieu 85 . Selective use of visible light with wavelengths of 405–425 also inactivates virus in a time‐dependent manner 86–88 . Chemical photosensitization enhances the effects of visible light spectra 89–91 .…”
Section: Irradiation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sunlight exposure may serve to decontaminate SARS‐CoV‐2 experimentally, but will depend on the specific virus milieu 85 . Selective use of visible light with wavelengths of 405–425 also inactivates virus in a time‐dependent manner 86–88 . Chemical photosensitization enhances the effects of visible light spectra 89–91 .…”
Section: Irradiation Methodsmentioning
confidence: 99%
“… 85 Selective use of visible light with wavelengths of 405–425 also inactivates virus in a time‐dependent manner. 86 , 87 , 88 Chemical photosensitization enhances the effects of visible light spectra. 89 , 90 , 91 It is conceivable that several variations of such exposure could contribute to further practical applications.…”
Section: Irradiation Methodsmentioning
confidence: 99%
“…For instance, a study suggested the application of a particular visible light spectrum for inactivating VHSV in fish (Ho et al., 2020). Blue light has also been found to be effective at reducing the infectivity of murine leukaemia virus and coronaviruses (Kocher et al., 2022; Richardson & Porter, 2005). Additionally, a particular light spectrum (405 nm) was successfully applied for controlling SARS‐CoV‐2, influenza A virus and feline calicivirus (Rathnasinghe et al., 2021; Tomb et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study suggested the application of a particular visible light spectrum for inactivating VHSV in fish (Ho et al, 2020). Blue light has also been found to be effective at reducing the infectivity of murine leukaemia virus and coronaviruses (Kocher et al, 2022;Richardson & Porter, 2005).…”
mentioning
confidence: 99%
“…Further, in the 16 J/cm 2 early feasibility trial, there were no application site reactions and no device-related serious adverse events reported [ 9 , 11 , 12 ]. Although these prior hazard assessments [ 10 , 13 ] and initial clinical safety analyses are necessary steps toward the development of acute oral cavity light-dosing devices, continuing to evaluate potential hazards (through preclinical studies) and clinical safety (through clinical trials) is necessary, particularly for the novel application of photomedicine in the oral cavity for which there is limited clinical precedent. For this reason, in this work we sought to perform a more systematic preclinical in vitro assessment of the various potential hazards that could result from delivering acute 425 nm light doses to the oral cavity.…”
Section: Introductionmentioning
confidence: 99%